Film Regulation and Censorship Practices in Saudi Arabia: A Case Study of GCAM - Alamri, Musab (Department of Communications, Universitas Islam Indonesia, 2023)
This article investigates the role of the General Commission for Audiovisual Media (GCAM) in the policymaking, regulation, and legislation related to the licensing and oversight of the Saudi film industry. It analyzes the regulatory history that led to the establishment of the GCAM and then examines how GCAM has managed the industry. It also explores GCAM’s two most significant activities: supporting the development of the film industry and censorship. Additionally, it seeks to determine whether GCAM is an overall contributor to or constraint on the industry in light of film censorship. The article examines the significant challenge GCAM faces in balancing openness and freedom of expression with its obligation to consider and respect Saudi society’s culture and traditions. This examination of GCAM reveals its role in film distribution and exhibition, censorship practices, and labor laws. As an oversight body, GCAM is responsible for media freedom. The findings reveal strict censorship, the high cost of film accessibility, and an absence of employment laws to protect film crews.